Horizons of Difference : Rethinking Space, Place, and Identity with Irigaray. - Crapo Kim, Ruthanne; Russell, Yvette; Sharp, Brenda (SUNY series in gender theory., 2022)
Edited collection engaging Luce Irigaray's work and pushing it in important new directions.